Evaluasi Fibrosis Hati Dengan USG, CT-Scan dan MR - Deasy Umi Hajarsari (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Liver fibrosis is a histological feature of most chronic liver diseases that can progress to cirrhosis, liver failure, and hepatocellular carcinoma. An accurate diagnosis of liver fibrosis is necessary to determine the prognosis, risk stratification, and treatment decision-making. In establishing the diagnosis of liver fibrosis can be done with invasive and non-invasive techniques. Liver biopsy, the reference standard for assessing liver fibrosis, is invasive, expensive, and impractical for surveillance and monitoring of treatment responses. Non-invasive examinations include ultrasound, CT-Scan and MR. This paper contains a picture of liver fibrosis found in various radiological modalities.